Early weight bearing in acetabular and pelvic fractures - Murena, Luigi; Canton, Gianluca; Hoxhaj, Bramir; Sborgia, Andrea; Fattori, Roberto; Gulli, Stefano; Vaienti, Enrico (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work: The incidence of pelvic and acetabular fractures is increasing during the years, counting 37 pelvic fractures per 100000 people annually. No weight bearing or toe touch weight bearing are usually chosen in the initial management to allow fracture and ligamentous healing and avoid fracture displacement and fixation failure. On the other hand, early weight bearing may stimulate fracture healing and allow prompt functional recovery, faster return to work and recreational activities and reduce complications linked to late rehabilitation. Aim of the study is to review the literature about weight bearing indications for pelvic and acetabular fractures to highlight clinical and biomechanical evidence supporting early weight bearing. Methods: Two independent reviewers independently extracted studies on early weight bearing of pelvic and acetabular fractures. All selected studies were screened independently based on title and abstract. Then the full text of any article that either judged potentially eligible was acquired and reviewed again. Any disagreement was resolved by discussing the full text manuscripts. Results: 44 studies including reviews, meta-analysis, clinical and biomechanical studies were selected. Conclusions: Despite biomechanical data, few clinical evidences can be found to support early weight bearing in pelvic and especially acetabular fractures treatment. The promising results of some clinical experiences, however, should direct further studies to clearly define the indications and limits of early weight bearing in these injuries. Recognizing intrinsic lesion stability and bone and fixation technique quality, together with patient age and compliance, should be the mainstay for post-operative management choice.